HUBUNGAN LITERASI KESEHATAN DENGAN PERILAKU MANAJEMEN DIRI PADA KELOMPOK HIPERTENSI DI WILAYAH KERJA PUSKESMAS PACELLEKANG KABUPATEN GOWA - Andi Mutiara Muthahharah; Rasdiyanah, Rasdiyanah; Fitriani, Aidah; Sutria, Eny; Mildawati, Titi (Universitas Islam Negeri Alauddin Makassar, 2024)
Hypertension is the main cause of premature death worldwide. Hypertension has become a global, regional, national, and local public health problem. The World Health Organization (2023) estimates that 1.28 billion adults aged 30-79 years worldwide suffer from hypertension. The prevalence of hypertension will continue to increase sharply. In 2025, it is predicted that around 29% of adults worldwide will suffer from hypertension. Hypertension has caused the deaths of around 8 million people each year. 1.5 million deaths occur in Southeast Asia, where one-third of the population suffers from hypertension (WHO, 2011). Hypertension requires proper self-management and health literacy in handling it. .Objective: The purpose of this study was to analyze the relationship between health literacy and hypertension management behavior in the hypertension group in the Pacellekang Health Center work area, Gowa Regency. Methods: This research was conducted in the working area of Pacellekang Health Center, Pattallassang District, Gowa Regency, South Sulawesi Province on June 21 – July 21, 2023. Correlational anality descriptive research design using a cross-sectional study approach. The population in this study was 165 people. Sampling technique using non-probability sampling with purposive sampling technique. The sample obtained is 128 people. Data collection used the HELIA Questionnaire (Health Literacy Instrument for Adults) and the HBP-SCP Questionnaire (High Blood Pressure-Self Care Profile). The analysis tests used in this study were univariate and bivariate. The bivariate analysis in this study was by using the Chi-Square Test. The results showed that the majority of respondents had low health literacy with a percentage of 56.3% and the majority had poor hypertension management behavior with a percentage of 54.7%. The results of the bivariate test using the Chi-Square test with a significance value of 0.006 <0.05, so that the better a person's health literacy, the better his hypertension self-management behavior. The conclusion of this study is there is a significant relationship between health literacy and hypertension management behavior in the community in the Pacellekang Health Center work area, Gowa Regency. Suggestions for research locations so that they can increase posyandu and prolanis activities while also implementing health promotion on GERMAS and CERDIK as a form of increasing interest in controlling hypertension for the community. In addition, health centers can also add health information sources. Keywords: Health Literacy, Hypertension, Management Behavior